Planning Financial Flows for Public Institutions - Ušpurienė, Ana; Sakalauskas, Leonidas; Dumskis, Valerijonas (Jaunųjų mokslininkų darbai, 2016)
The paper deals with planning financial flows for public institutions. The main financial management instruments have been described and multi-stage cost minimization models have been created. Constraints for financial instruments and their combinations are presented in the paper. The developed models were used to solve two-stage and multi-stage optimization of financial flows tasks at the Institute of Mathematics and Informatics, Šiauliai University. Mixed-integer programming algorithm was embeded in the developed model, CPLEX Studio software package was embeded for optimization. The results from two-stage and multi-stage tasks were compared.